SUGGESTED CORRECTIONS TO TEXTBOOK ENTITLED: “LANCAR NGOBROL MANDARIN UNTUK WISATA” - Sudono Noto Pradono (Widya Mandala Surabaya Catholic University, 2016)
The aim of this article is to suggest corrections to a published book. The writer analyzed a book entitled “Lancar Ngobrol Mandarin untuk Wisata” (“Fluently Speaking Chinese for Tourism”). The writer found many mistakes in this book, which he classified as follows: 1. phonetics, 2. characters, 3. choice of words. The mistakes are discussed and the corrections are suggested. Therefore, the writer suggests that becoming Chinese book writers should have a sufficient knowledge, so that such kind of mistakes will not happen.